Proceedings of the 2nd International Workshop on AI in Society, Education and Educational Research (AISEER 2025) co-located with 28th European Conference on Artificial Intelligence (ECAI 2025). Bologna, Italy, October 25, 2025 - Dörpinghaus, Jens [Herausgeber]; Tiemann, Michael [Herausgeber]; Helmrich, Robert [Herausgeber] (My University, 2025)
The Proceedings comprise the 13 papers that were accepted for the 2nd International Workshop on AI in Society, Education and Educational Research (AISEER 2025) that was a part of the 28th European Conference on Artificial Intelligence (ECAI 2025). "This workshop has two distinct foci with the aim of facing the field of AI in society and education in a wider manner. The first one is more technical, focused on the issues of applying AI methods in society and education, while the second will open up to a more interdisciplinary perspective, including social and educational perspectives of the use of AI in education. In both perspectives, it is essential that the different disciplines, actors, and stakeholder communicate and understand each other, which is also one of the goals of this workshop. More broadly, we are interested in how AI methods affect all areas of society, education, as well as businesses and labor markets. This includes approaches to how all sectors of education, from primary to tertiary, are affected by and respond to AI methods. While digital methods and AI are emerging topics in these fields, this workshop is not limited to discoveries in these areas, but is also dedicated to reflecting on methods and results in the field of AI." (Editors, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; 370; 300; Künstliche Intelligenz; Bildungsforschung; Sozialwissenschaft; Interdisziplinäre Forschung